Tradisi Nganyari Nikah sebagai Bentuk Adaptasi Sosial: Reaktualisasi Ikatan Perkawinan dalam Keluarga Pekerja Migran di Margorejo Kendal - Nurul Firdaus Firdaus; Bustanul Arifien Rusydi; Zahri Sofyan Aljibra; Muh Ubaidillah; Syaf Zidan Tamama (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
Labor migration has transformed family dynamics in many rural communities, creating social challenges that require adaptive mechanisms to maintain family resilience and social stability. In Indonesia, one such mechanism is reflected in the Nganyari Nikah tradition, a practice of renewing marital bonds that continues to be maintained among some migrant workers' families. Although this tradition has been widely examined from the perspective of Islamic normative law, its function as a mechanism of social adaptation has received limited scholarly attention. This study aims to analyze the social, cultural, and religious factors underlying the emergence and continuity of the Nganyari Nikah tradition, examine its implementation among migrant workers' families, and explore patterns of social adaptation through Talcott Parsons' Social Adaptation Theory. This study employed a descriptive qualitative design with a sociological approach in Margorejo Village, Cepiring District, Kendal Regency, Indonesia. Data were collected from 13 purposively selected informants, comprising six migrant worker couples (12 individuals) and one Lebe (village religious official), through in-depth interviews, observation, documentation, and literature review. The collected data were then analyzed using qualitative methods. The findings indicate that the continuity of the Nganyari Nikah tradition is shaped by labor migration practices, local interpretations of taklik talak (conditional divorce pledge), and the strategic role of the Lebe and the local community in maintaining social order. The analysis identifies four distinct patterns of social adaptation: restorative adaptation, preventive adaptation, proactive adaptation, and reconciliative adaptation. Building on Talcott Parsons' Social Adaptation Theory, these findings propose a fourfold typology of social adaptation as a preliminary analytical framework for understanding how local traditions function as adaptive mechanisms to strengthen family resilience and social stability within migrant worker communities